Effect of supplementary physical training on vertical jump height in professional ballet dancers - Escobar-Álvarez, J. A.; Jiménez-Reyes, P.; Da Conceição, F. A.; Fuentes-García, J. P. (International Journal of Sports Physiology and Performance, 2022)
Dancers require many specific dance skills of a ballistic nature. The design of supplementary training to improve the strength of the lower limbs and jump height is a relevant area of research. The purpose of this study was (1) to compare the effect of plyometric training versus combined training on countermovement jump (CMJ), squat jump (SJ), and sauté in first position (sauté) height and (2) to observe whether changes in CMJ and SJ were associated with changes in sauté in female and male dancers. Eighty-one classical professional ballet dancers (41 women and 40 men, age = 22.9 [3.7] y, body mass = 59.7 [8.6] kg, height = 167.4 [7.3] cm) were divided into a control group and 2 experimental groups: plyometric training and combined training. All groups followed their common routine of training regarding classes and rehearsal practice, whereas the experimental groups added 2 sessions (1 h per session) for 9 weeks of supplementary training. Significant increases (medium to large effect size) in CMJ, SJ, and sauté height were found in the pretest versus posttest comparisons for both experimental groups. Significant, very large correlations were found between the magnitude of improvement in sauté and the magnitude of improvement in CMJ and SJ. Plyometric and combined training programs are effective ways to improve jumping ability in professional dancers. The improvement in CMJ and SJ has a good transference on sauté `performance. These findings support the use of traditional training methods to improve jump height in specific and nonspecific ballet jumping ability.